Levels of identity related to landscapes - Csorba, Péter (JOURNAL OF LANDSCAPE ECOLOGY, 2010)
The natural and transformed cultural landscapes both play an important role in forming our personal, collective, national or nationality but still continental identity as well. In recent years – to clearly counterbalance the globalisational tendencies – reinforcing raillery to place, environment and landscape has also been incited institutionally in Europe (European Landscape Convention). It is recognised namely identity frees forces improving quality of life. It has a positive share in social development from small communities to continental level. The individual landscape identity often tends to landscapes and landscape fragments being less valuable landscape aesthetically and ecologically. On the other hand the higher level community the concrete landscape is the object of the identity of the more the aesthetical quality and the historical importance play role in. The historical development of several European landscapes has followed closely the general social and economical development for centuries. This results the so-called strong landscape coherence level, and these landscapes are especially suitable to produce a high degree of identity sentiment from their inhabitants.The development of identity sentiment attaching to landscapes can be studied on several communal levels. Strengthening the “being European sentiment” is quite new among these. Especially small nations having been delivered from foreign oppression experience the different forms of national identity – for example fostering the characteristic national landscapes.The landscape character, the object of the landscape identity, mainly manifests in the visual appearance of landscapes. But there are a lot of examples concerning some smellscapes and soundscapes which are inseparable parts of landscape identity.There are initial efforts to measure identity being connected with landscapes. Several scientific projects make trials of finding proper indicators. Amongst these besides aesthetical attractivity certain geographical data seem to be utilizable, e.g. landscape use permanence, the ratio of the traditional land use, building up density, the edge effect index of landscape pattern, etc.
Keywords: personal, national and European landscape identity